Beyond post-traumatic stress : homefront struggles with the wars on terror - Hautzinger, Sarah J., 1963-; Scandlyn, Jean. (Walnut Creek, California : Left Coast Press Inc., 2014)
"When soldiers at Fort Carson were charged with a series of 14 murders, PTSD and other "invisible wounds of war" were thrown into the national spotlight. With these events as their starting point, Jean Scandlyn and Sarah Hautzinger argue for a new approach to combat stress and trauma, seeing them not just as individual medical pathologies but as fundamentally collective cultural phenomena. Their deep ethnographic research, including unusual access to affected soldiers at Fort Carson, also engaged an extended labyrinth of friends, family, communities, military culture, social services, bureaucracies, the media, and many other layers of society. Through this profound and moving book, they insist that invisible combat injuries are a social challenge demanding collective reconciliation with the post-9/11 wars"--
Part I: Soldiers Coming Home -- 1. PTSD = Pulling the Stigma Down -- 2. "It's Just a Job" -- 3. Lethal Warriors at Home -- 4. Decentering PTSD: A War Outgrows a Diagnosis -- Part II: War's Labyrinth at Home -- 5. Codeswitching and Sticky Switches: Navigating Absence and Presence -- 6. "Under the Chain of Command" : Spouses' Volunteer Work -- 7. Waiting to Serve -- Part III: Dialog -- 8. "Best Hometown in the Army" -- 9. "Clueless Civilians" and Others --10. "Closing the Gaps" : Seeking Military-Civilian Dialog -- Conclusion: War and Collective Reckoning.
Includes bibliographical references (pages 280-303) and index.
Machine generated contents note: IntroductionPart I: Coming Home 1. Lethal Warriors at Home 2. "Best Home Town in the Army"3. Doing Dirty Work4. PTSD = Pulling the Stigma Down 5. Decentering PTSD Part II: The Supporting Cast 6. Codeswitching : "So, why do you have frostbite?" 7. "This is Our Playground": Family Readiness Groups 8. Waiting to Serve 9. Appropriate Accommodation, or Exceptionalism for Supercitizens? 10. "This Land is Not for Sale": on Canyon and Army Expansionism Part III: Dialogue 11. "You're Not a Victim, You're a Volunteer" 12. "Closing the Gaps": Seeking Civilian-Military Dialogue 13. "Clueless Civilians" and Others 14. The Day after Veterans Day: Listening to the Homefront Conclusion: Toward a Collective Reckoning with the Post-9/11 WarsReferencesIndex.
Keywords: Post-traumatic stress disorder; Post-traumatic stress disorder -- Patients -- United States; Veterans -- Mental health -- United States; Iraq War, 2003-2011 -- Psychological aspects; Afghan War, 2001-2021 -- Psychological aspects; War on Terrorism, 2001-2009 -- Psychological aspects